Transplant Renal Artery Stenosis: A Case Report and Literature Review - Simforoosh, Nasser; Nayebzade, Amirhossein; Ghaedi, Meisam (Urology Journal, 2024)
Transplant renal artery stenosis is the most common vascular complication that occurs following kidney transplantation and can lead to graft dysfunction and even its loss. The present report describes A patient with endstage renal disease who underwent living related renal transplantation. He had oliguria and creatinine rise in the post-operative course but all doppler ultrasonography (DUS) during the 2 months post-operation for the renal graft showed a normal mean resistive index in the graft renal artery. Hemodialysis treatment started and continued for 4.5 months. On post-operative day 137, because of the patient’s anuria and resistant hypertension, another DUS carried out and reported evidence that suggested arterial stenosis. A computed tomographic (CT) renal angiogram showed a small filling defect in the proximal graft artery that was highly suggestive for transplant renal artery stenosis (TRAS). Following angiography revealed a short linear stenosis. Endovascular intervention and stent placement were performed successfully for the patient on post-operative day 139. This case was initially diagnosed as ongoing acute rejection for which he received antirejection therapy without any significant improvement. After percutaneous transluminal angioplasty (PTA), serum creatinine trended down and urine output improved within 12 h, and they were stable at one-year follow up with a good renal function. It was noteworthy that, despite after a 4.5-month delay in diagnosis and maintenance need for dialysis, the patient responded to endovascular treatment and the graft function became normalized. Our case demonstrates that graft can be saved even if renal artery stenosis is diagnosed after several months of dialysis and diagnosis of end stage renal disease post transplantation.